The Effects of Digital Banking on Customer Experience, Customer Satisfaction, and Customer Loyalty in Morocco - Bouafi, Samia (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
The aim of this study is to examine the factors affecting customer satisfaction and their intentions towards using digital banking services in Morocco. Six factors were used in this study: functional quality, brand trust, privacy, security, enjoyment and attitudes as well as demographic variables. To collect data, 300 questionnaires were distributed from which 260 were completed and analyzed. Required analysis have been done using SPSS 20.0. The findings of this research showed that functional quality, brand trust, enjoyment, and attitudes of customers positively and significantly impact customer satisfaction. Moreover, it was also found that functional quality, attitudes, and customer satisfaction, positively and significantly impact the behavioral intentions of customers towards digital banking services. This study attempts to gather the most important factors affecting the use of digital banking services in Morocco since there are few researches conducting such a study. Keywords: digital banking, customer satisfaction, customers’ intentions, Morocco.

ÖZ: Bu çalışmanın amacı, Fas'ta müşteri memnuniyetini etkileyen faktörleri ve dijital bankacılık hizmetlerini kullanmaya yönelik niyetlerini incelemektir. Bu çalışmada altı faktör kullanılmıştır: fonksiyonel kalite, marka güveni, mahremiyet, güvenlik, zevk ve tutumlar ile demografik değişkenler. Veri toplamak için, 260'ı doldurulmuş ve analiz edilmiş 300 anket dağıtılmıştır. SPSS 20.0 kullanılarak gerekli analizler yapılmıştır. Bu araştırmanın bulguları, fonksiyonel kalite, marka güveni, müşteri memnuniyeti ve müşteri tutumlarının müşteri memnuniyetini olumlu ve önemli ölçüde etkilediğini göstermiştir. Ayrıca fonksiyonel kalitenin, tutumların ve müşteri memnuniyetinin müşterilerin dijital bankacılık hizmetlerine yönelik davranış niyetlerini olumlu ve önemli ölçüde etkilediği tespit edilmiştir. Bu çalışma, Fas'ta dijital bankacılık hizmetlerinin kullanımını etkileyen en önemli faktörleri toplamaya çalışmaktadır, çünkü böyle bir çalışma yapan çok az araştırma vardır. Anahtar Kelimeler: Dijital bankacılık, müşteri memnuniyeti, müşterilerin niyeti, Fas.
Master of Arts in Marketing Management. Institute of Graduate Studies and Research. Thesis (M.A.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2020. Supervisor: Prof. Dr. Mehmet Haluk Köksal
Keywords: Industrial Engineering; Banks and Banking--Customer relations--Quality Management--Marketing management--Morocco; Consumer Satisfaction--Customer Loyalty--Marketing Management--Morocco; Customer Relations--Marketing Management; Customer services--Evaluation; Digital banking; customer satisfaction; customers’ intentions; Morocco